PENENTUAN AKTIVITAS 60CO DAN 137CS PADA SAMPEL UNKNOWN DENGAN MENGGUNAKAN DETEKTOR HPGe - Miftahul Aziz; Eko Hidayanto; Diah Dwiana Lestari (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2015)
The measurement of radioactivity 60Co and 137Cs in the unknown sample were conducted to determine activity value using HPGe detector. Calibration of energy, calibration efficiency, making the efficiency of the curve calibration, and validation methods are the determination of sample source activity. Calibration of energy and efficiency using standard sources QCRB 1186 and 152Eu. Enumeration carried out using two detectors with efficiencies of 25% and 35%, respectively at a distance of 17 cm and 24 cm. Efficiency curve created using the excel program. Determination of activity is carried out by chopping Co and Cs in the unknown sample at the same position as the standard source for 3600 seconds. Method validation is done by calculating the activity of standard source QCRB 1186 and 152Eu. Method validation using standard source 152Eu at a distance of 17 cm provide a bias of 1,4% - 3,6% and at a distance of 24 cm provide a bias of 0,3% - 4,6%. Determination of activity the unknown sample against reference value at a distance of 17 cm (Co 1173 keV: 16125 Bq and 16716 Bq; Co 1332 keV: 16526 Bq and 16287 Bq; Cs 662 keV: 16526 Bq and 16287 Bq) and at distance of 24 cm (Co 1173 keV: 15289 Bq and 16533 Bq; Co 1332 keV: 15477 Bq and 16481 Bq; Cs 662 keV: 37226 Bq and 38540 Bq). Keywords: Activity, 60Co, 137Cs, Calibration efficiency, Method Validation